Viral gene expression profile of goose haemorrhagic polyomavirus in susceptible primary cells. Issue 5 (3rd September 2021) - Kaszab, Eszter; Szabadi, Luca; Kepner, Anett; Bajnóczi, Pál; Lengyel, György; Bányai, Krisztián; Fehér, Enikő
ABSTRACT: Routine culturing of goose haemorrhagic polyomavirus (GHPV) is cumbersome, and limited data are available about its replication and gene expression profile. In this study, goose embryo fibroblast cells were infected with GHPV for temporal measurement of the viral genome copy number and mRNA levels with quantitative PCR. Accumulation of small and large tumour antigen-encoding mRNAs was detected as early as 9 hours post-infection (hpi), while high level expression of the capsid protein encoding VP1-VP3, and ORF-X mRNAs was first detected at 24 hpi. Elevation of GHPV genome copy number was noted at 48 hpi. The results indicate that the gene expression profile of GHPV is similar to that described for mammalian polyomaviruses. RESEARCH HIGHLIGHTS GHPV was propagated in culture of primary goose embryo fibroblast cells. The transcription commenced before the onset of viral DNA replication. The transcription patterns of GHPV and mammalian polyomaviruses were comparable.